The relationship of soundscape and shopping behaviors in Malioboro Mall and Ambarrukmo Plaza, Yogyakarta - Verza Dillano Gharata; Sushardjanti Felasari; Prasasto Satwiko; Brigitta Michelle (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
This study investigates the acoustic comfort of shopping malls related to the standards and people's emotions. The soundscape is vital in shopping malls to attract more visitors. This research studied the soundscapes of two shopping malls in Yogyakarta, focusing on the effect of noise on the environmental perceptions of hedonic and utilitarian consumers. The research took on-site noise measurements to create soundscapes maps. There were also interviews to explore their opinions about the noise inside malls. Data were statistically analyzed using Statistical Package for the Social Science. The results showed that only some soundscape elements affected arousal emotions among hedonic consumers, concerning a more extensive period of mall visits. No soundscape element affected pleasure emotions among utilitarian consumers with the length of stay in malls. Socio-cultural backgrounds of shopping culture (in traditional and modern markets) and soundscape conditions were also considered. The excessive soundscapes did not directly impact the health negatively of those who spent long periods in malls. The subsequent studies may continue to find the relation between acoustic comfort and the difference with the regulation.